2017
DOI: 10.1080/17425255.2017.1396317
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron: a review of pharmacokinetics and clinical experience in chemotherapy induced - nausea and vomiting

Abstract: Chemotherapy induced nausea and vomiting (CINV) are major side effects of chemotherapy and a great burden to patients' quality of life. Serotonin and substance P are the major neurotransmitters involved in the pathophysiology of CINV, but in spite of new antiemetics no completely effective regime exists for its prevention or treatment. Areas covered: In this review the authors provide a detailed description of granisetron's chemistry pharmacokinetics, pharmacodynamics, toxicity and a brief review of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…In the present study, we observed a decrease in heart rate of dogs in the granisetron group, started 30 minutes after the intervention and continuing for 2 hours, though being insignificant. We hypothesize that granisetron can decrease the heart rate through blocking serotonin receptors on the afferent vagus nerve in the gastrointestinal tract and the feedback mechanism (Buyukavci et al 2005;Spartinou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed a decrease in heart rate of dogs in the granisetron group, started 30 minutes after the intervention and continuing for 2 hours, though being insignificant. We hypothesize that granisetron can decrease the heart rate through blocking serotonin receptors on the afferent vagus nerve in the gastrointestinal tract and the feedback mechanism (Buyukavci et al 2005;Spartinou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Varying pharmacologic properties of different 5‐HT 3 receptor antagonists impede comparison. Granisetron has a plasma half‐life of approximately 4.2–6.1 hours, which increases among elderly patients (>65 years); 12% of this drug is excreted unchanged via urine, with the remainder metabolized by the liver . By contrast, the plasma half‐life of ondansetron is 3.5 hours, increasing up to 5.5 hour among the elderly (age >75 years); this drug is also mainly metabolized by the liver .…”
Section: Discussionmentioning
confidence: 99%
“…Common side effects include headache (10%–15%), constipation (2%–4%), lethargy (2.5%–5%), diarrhea (0.6%–2%), and dizziness (0.5%–3.2%). [14] According to reports, the 5-HT3 receptor inhibitor may also prolong the QT interval of the heart, but this is very rare. [16] However, reports of side effects in granisetron in critically ill patients are lacking.…”
Section: Methodsmentioning
confidence: 99%
“…Granisetron is a highly selective 5- hydroxytryptamine 3 (5-HT3) receptor antagonist that has been widely used clinically to treat vomiting after chemotherapy with mild side effects, high safety, and low cost. [14] Theoretically, for patients with sepsis, supplementation with granisetron may be an effective treatment for reducing organ damage and improving the survival rate of patients. However, there is no clinical evidence for whether granisetron can greatly improve the prognosis of patients with sepsis than a placebo.…”
Section: Introductionmentioning
confidence: 99%